Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Sections 9.1-9.6 - Integrated Review - Functions and Properties of Logarithms: 15

Answer

$ f^{-1}(x)=\frac{x-2}{3}$

Work Step by Step

We are given the function, $f(x)=3x+2$. First, we must replace $f(x)$ with y. $y=3x+2$ Next, interchange x and y. $x=3y+2$ Next, solve for y by subtracting 2 from both sides. $3y=x-2$ Divide both sides by 3. $y=\frac{x-2}{3}$ Finally, replace y with $f^{-1}(x)$. $ f^{-1}(x)=\frac{x-2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.